Is transport distance correlated with animal welfare and carcass quality of reindeer (Rangifer tarandus tarandus)? - Laaksonen, Sauli; Jokelainen, Pikka; Pusenius, Jyrki; Oksanen, Antti (BioMed Central, 2017)
Abstract Background Slaughter reindeer are exposed to stress caused by gathering, handling, loading and unloading, and by conditions in vehicles during transport. These stress factors can lead to compromised welfare and trauma such as bruises or fractures, aspiration of rumen content, and abnormal odour in carcasses, and causing condemnations in meat inspection and lower meat quality. We investigated the statistical association of slaughter transport distance with these indices using meat inspection data from years 2004–2016, including inspection of 669,738 reindeer originating from Finnish reindeer herding areas. Results Increased stress and decreased welfare of reindeer, as indicated by higher incidence of carcass condemnation due to bruises or fractures, aspiration of rumen content, or abnormal odour, were positively associated with systems involving shorter transport distances to abattoirs. Significant differences in incidence of condemnations were also detected between abattoirs and reindeer herding cooperatives. Conclusions This study indicates that in particular the short-distance transports of reindeer merit more attention. While the results suggest that factors associated with long distance transport, such as driver education, truck design, veterinary supervision, and specialist equipment, may be favourable to reducing pre-slaughter stress in reindeer when compared with short distance transport systems, which occur in a variety of vehicle types and may be done by untrained handlers. Further work is required to elucidate the causal factors to the current results.